Candida species isolated from clinical samples in a tertiary hospital in Honduras: Where is Candida auris? - Bryan Ortiz; Kateryn Aguilar; Celeste Galindo-Morales; Lizzy Molina; Gustavo Fontecha (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Infections by emerging and multiresistant Candida species are becoming more frequent throughout the world. This study aimed to describe Candida species in different wards of a tertiary hospital in Honduras. Materials and Methods: Prevalence of species within the C. albicans complex was estimated using a molecular approach, and C. auris was investigated using a yeast pool-based DNA extraction method. Three hundred and twenty-eight yeast isolates were identified using phenotypic approaches. For identification of species within the albicans complex, a molecular approach based on the size polymorphisms of the hpw1 gene was used. In addition, we optimized a technique based on DNA extraction in pools for the rapid identification of C. auris. Results: Eleven species of Candida were identified in the hospital wards. Candida albicans showed the highest number of isolates (52.4%). Within the Candida albicans complex, C. albicans sensu stricto was the most common followed by C. dubliniensis. C. auris was not found. Conclusion: Reports on the distribution of Candida species in Honduras are limited, thus the data from this study are of importance for a better understanding of their epidemiology. Also, we offer a simple method for the detection of C. auris that could help in its detection in low-resource settings.